ChemInform Abstract: Direct Vicinal Difunctionalization of Alkynes: An Efficient Approach Towards the Synthesis of Highly Functionalized Fluorinated Alkenes. Issue 24 (June 2015) - Besset, Tatiana; Poisson, Thomas; Pannecoucke, Xavier
Abstract: Review: [92 refs.